Unveiling the Nexus of Industrialisation and Trade in Eastern and Southern Africa: A Comprehensive Analysis - (:unkn) unknown (My University, 2024)
Abstract: This article scrutinises the intricate relationship between industrialisation efforts and trade performance in the Eastern African Community (EAC) and Southern African Development Community (SADC) regions. Leveraging secondary review methodology, it explores the impact of industrialisation initiatives on trade dynamics, as outlined in the EAC Industrialisation Policy 2012-2032 and SADC Industrialisation Strategy 2015-2063. It serves as a foundation for formulating and implementing policies that can effectively harness the benefits of industrialisation to drive trade performance and promote sustainable economic development in the Eastern and Southern African regions. The literature review findings and the analysis demonstrate the significant potential of industrialisation efforts, guided by the EAC Industrialization Policy 2012-2032 and SADC Industrialization Strategy 2015-2063, to promote trade performance in these regions. The analysis also reveals a disconnect between industrialisation endeavours and trade diversification.Furthermore, the study has identified specific areas where policy interventions can further enhance the positive outcomes of industrialisation efforts on trade performance within the EAC and SADC regions. This includes recommendations for strengthening infrastructure, encouraging technology adoption and innovation, streamlining trade facilitation processes, investing in capacity building and skills development, fostering regional integration, and emphasising environmentally sustainable industrial practices.
Keywords: African Research